The Sami National Day as a Prism to Tromsø Sami Identity: the Past and the Present - Kharina, Valentina (Universitetet i Tromsø, 2013)
The thesis “The Sami National Day as a Prism to Tromsø Sami Identity: the Past and the Present” researches the way Tromsø Sami identity has changed over the last 20 years. The institution of the Sami National Day is used as a shaping tool of the concept of identity. In this work I investigate the way the celebration of Sami Day has changed since the time the holiday was established in 1993 up to nowadays: in the past the celebration had a small-scale, local, character, uniting a limited number of the Sami people and their friends, while today the Sami National Day unites the whole city and is celebrated not only by the Sami - the number of which has significantly increased - but also by foreigners and Norwegians living in the city. On the basis of this analysis I research the way Tromsø Sami identity has developed over the last 20 years: it has become much more visible in society and stronger. Moreover, I investigate the issue of the level of development according to my research model Tromsø Sami identity is today. The research is based on 22 interviews and has primarily qualitative character. Therefore, the results of the research can’t reflect the whole Tromsø Sami community but they show the readers some patterns in it.